Basic Capital in the Egalitarian Toolkit?. Issue 4 (1st June 2015) - White, Stuart
Abstract: Under a basic capital grant policy (BC), every citizen receives a large capital grant as a right, typically in their early adulthood. Is BC part of the institutional framework of a just economy? Starting from John Rawls's discussion of just economic systems, this article clarifies Rawls's reasons for thinking we need to complement welfare state policies with property‐owning democracy and/or liberal socialist policies. It then seeks to clarify the grounds specifically for BC as a particular policy of the property‐owning democracy type, and considers in depth what it adds to a policy of basic income (a uniform, universal and unconditional income grant paid to all, possibly in some part as a share of the return on publicly‐owned wealth).